Marketing and the internet - Hamill, Jim (Henry Stewart Talks, 2012)
Web 2.0/Social media, Business/Marketing 2.0, The social media revolution, Potential business benefits of social media, Approach to social media, Social media vs. social business, Key things about social media, Winners in social media, Avoiding the road to nowhere, The key to having a good conversation, Being 'customer-led', Social media listening and its business benefits, Where & what conversations to monitor, Tools available to help, Converting information into action, Social media strategy and action plans
Archived at 2022/04/26